Duration of Whole-Body Air-Cryo-Exposure (–120°C) Affects Some Properties of Murine Erythrocytes - Kudokotseva, Olga V.; Kovalenko, Igor F.; Lomakin, Ivan I.; Babijchuk, Georgiy A. (Problems of Cryobiology and Cryomedicine, 2017)
An influence of whole-body air-cryo-exposure (ACE) (–120°C) performed in cryochamber for experimental animals rendered on the populations, osmotic fragility and the hemolysis level in erythrocytes of peripheral blood (PB) of mice was studied. The analysis of our findings showed that the duration of one session of ACE (40, 60 and 90 sec) affected the qualitative and quantitative composition of erythrocytes, i. e.their total number in the PB was reduced, in particular on an account of discocytes, the part of reversibly modified forms (stomatocytes) was significantly increased. Whole-body ACE led to an increased osmotic fragility and elevated hemolysis of erythrocytes. An hour following the ACE we have not found any normalization in quantitative and population composition of erythrocytes of mice PB. Thus the observed effect, rendered by a whole-body cooling on the hemolysis in erythrocytes, enabled to state that the longer (60 and 90 sec) staying of the animals at –120°C had less impact on erythrocytes comparing to whole-body short-term extreme cooling of mice for 40 seconds. Probl Cryobiol Cryomed 2017; 27(1): 29–40